Strategi Dakwah Kultural Muhammadiyah Dalam Mengimplementasikan Nilai - Nilai Pendidikan Islam Di Masyarakat (Studi Empirik Pengurus Ranting Muhammadiyah Kelurahan Ngadirejo Kecamatan Kartasura Tahun 2016) - Suryanto, Joko; , Drs. M.Yusron, M.Ag (2016)
Muhammadiyah is a religious proselytizing organization of Islam which has put its struggle namely 'amar ma'ruf nahī munkar that uses society as object of its struggle. The effort of religious proselytizing of Muhammadiyah is done by teaching and giving Islamic values for aiming Islam as rahmatallil'ālamīn. In the effort to reach that, so it is needed precise religious proselytizing strategy so the aim which is hoped can be reached. Religious proselytizing cultural is one of education media which is chosen by Muhammadiyah to confront reality of society which is too complexes, cultural varieties, religion and development of world which always increases. This strategy is very important for Muhammadiyah as the education media in implementing education Islamic values by understanding heterogeneous society structure. There are problem statements of this study namely how are the religious proselytizing strategy as way for education which is done by Official of Ranting Muhammadiyah in Ngadirejo at implementing Islamic values for society during 2016, and what are obstacles which are found in the religious proselytizing effort. Moreover, the aims of this study are describing religious proselytizing strategy as the way for education which is done by Official of Ranting Muhammadiyah in Ngadirejo and describing what are obstacles which are found. The type of this study is observation. This study uses qualitative approach by using descriptive analysis method. Location of this study is in the Official of Ranting Muhammadiyah in Ngadirejo Kartasura. The method for collecting data uses interview, documentation, and observation. Furthermore, to analyze the result of the study, is used analysis approach of descriptive qualitative which consists of four events namely reviewing all the data from some sources (interview, observation and documentation), doing reduction for the data, presenting the data in the form of narration, and drawing conclusion. The result of this study shows that religious proselytizing strategy which is used by Official of Ranting Muhammadiyah as education media is by building Islamic Center as the form of the integration of Moslem. In the other hand, it is also by Amal Usaha Muhammadiyah namely Institution of Kindergarten Education Aisiyah to teach Islamic education since early. The other activity in the effort for teaching education values in society is by doing daily agenda of recitation in Sunday morning to learn about Nailul Authar, recitation in every Wednesday night, and recitation in every date of 12th, and also social society activity. That effort is also supported by technology progress which is used by Official of Ranting Muhammadiyah in Ngadirejo. Religious proselytizing cultural as education media is rather successful in doing the teaching education Islamic values for society. It can be seen that there are not friction between religion, and congregation of prayer which is called as jamaah sholat and increasing of recitation.